2017
DOI: 10.1098/rsob.170055
|View full text |Cite
|
Sign up to set email alerts
|

DictyosteliumAMPKα regulates aggregate size and cell-type patterning

Abstract: Starved Dictyostelium cells aggregate into groups of nearly 105 cells. AMPK is a highly conserved serine/threonine protein kinase consisting of a catalytic and two regulatory subunits. As multi-cellular development in Dictyostelium is initiated upon starvation, we explored the role of the energy sensor, AMPK, which shows significant similarity to human AMPK and is expressed throughout development. Deletion of the ampkα gene results in the formation of numerous small-sized aggregates that develop asynchronously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 58 publications
2
33
1
Order By: Relevance
“…Finer anatomy of wildtype and ampkα − fruiting bodies revealed alteration in stalk cell arrangements. Earlier, we showed that AMPKα gets activated upon starvation (Maurya et al, 2017) therefore we were interested to find whether deletion of ampkα rendered cell survival during starvation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finer anatomy of wildtype and ampkα − fruiting bodies revealed alteration in stalk cell arrangements. Earlier, we showed that AMPKα gets activated upon starvation (Maurya et al, 2017) therefore we were interested to find whether deletion of ampkα rendered cell survival during starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown in HL5 medium with or without the appropriate antibiotics (G148 or blasticidin). Dictyostelium cells were transformed by the electroporation method and ampkα null cells used in this study were prepared in our previous study (Maurya, Kumar, & Saran, 2017).…”
Section: Dictyostelium Growth Development and Transformationmentioning
confidence: 99%
“…Briefly, the logarithmic phase cells (3-5x10 6 cells ml -1 ) were used for inoculating the secondary culture at a starting density of approximately 5x10 5 cells ml -1 and monitored over several days. Development analyses were performed according to Maurya et al, (2017). The logarithmic phase cells were harvested, washed in 1xKK 2 buffer and spotted at a density of 5x10 7 cells ml -1 on non-nutrient agar (NNA) plates.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cutured in axenic medium HL5 at 22 o C (with or without G418) under shaken conditions according to Maurya et al, (2017) and proliferation was monitored according to Mishra et al, (2017).…”
Section: Strains and Developmentmentioning
confidence: 99%
“…Protocols for RNA isolation and RT-PCR (Reverse transcriptase-polymerase chain reaction) were followed as previously described (Maurya et al, 2017). Following cDNA synthesis, RT-PCR reactions were performed using gene-specific primer pairs ( Supplementary Table S1) for various genes.…”
Section: Treatment With Mgbg and Spermidinementioning
confidence: 99%